Sinkretisme dalam Novel Laskar Kesanghyangan Karya Kusyoto - Muhammad fajar; M. Shoim Anwar (Buana Bastra, 2018)
This research was motivated by the literary works to lift and offers a variety of issues and religious values in a novel environment. A work Satra can not escape from thecondition of society and cultural situation in a region where the literature was comingfrom. This study describes the theory of syncretism that include belief in a religion, thereligious values contained in the novel, the social aspect, legal aspect, in the novel LaskarKesanghyangan Kusyoto work. All aspects are related to the aspects of life. Data researchis using descriptive qualitative research because this study is not concerned with thenumbers and the data obtained an overview of the research’s object. Research data has asource which a novel untitled Laskar Kesanghyangan Kusyoto’s work. While the researchobject is any dialog or sentence that contains theory and elements of syncretism of thenovel.